Регуляторная политика Казахстана: проблемы и перспективы - Baizakov, S.B.; Tulepbekova, A.E.; Asenova, А.А.; Perdebayeva, R.S. (BUKETOV BUSINESS REVIEW, 2017)
The article has so been designed to explore the challenges in the way of implementing «smart regulation» in Kazakhstan. The paper contains a comprehensive analysis of the country’s regulatory policies over the recent ten years. The authors have carried out science-driven forecasts of future perspectives and trends in the long term development of Kazakhstan's regulatory policies. In addition, the paper has configured the role of public regulation in entrepreneurial activities. In this regard, the authors have found that the key role of public regulation may not only be in an overall reduction of the administrative burden for businesses and ensuring transparency of business operations but also in the reduction of public expenditures, enabling favorable business environment and increasing the contribution of small and medium size enterprises to economic development. The analysis concluded that Kazakhstan has achieved a considerable progress yet some bottlenecks still exist in implementing the regulatory system of management, efficiently. Besides, the implementation of smart regulation principles in Kazakhstan has enabled the construction of the complex system for adopting the decisions that reflect societal interests. It has also enabled the removal of administrative constraints and establishment of prerequisites, necessary for adopting simple, understandable and more transparent decisions.